Face of Murder (A Zoe Prime Mystery-Book 2) - Blake, Pierce (Lukeman Literary, 2020)
"A MASTERPIECE OF THRILLER AND MYSTERY. Blake Pierce did a magnificent job developing characters with a psychological side so well described that we feel inside their minds, follow their fears and cheer for their success. Full of twists, this book will keep you awake until the turn of the last page." --Books and Movie Reviews, Roberto Mattos (re Once Gone) FACE OF MURDER is book #2 in a new FBI thriller series by USA Today bestselling author Blake Pierce, whose #1 bestseller Once Gone (Book #1) (a free download) has received over 1,000 five star reviews. FBI Special Agent Zoe Prime suffers from a rare condition which also gives her a unique talent-she views the world through a lens of numbers. The numbers torment her, make her unable to relate to people, and give her a failed romantic life-yet they also allow her to see patterns that no other FBI agent can see. Zoe keeps her condition a secret, ashamed, in fear her colleagues may find out. When women are found murdered, their bodies branded with mysterious numbers, outside Washington, D.C., the FBI, stumped, calls in Special Agent Zoe Prime to decipher the mathematical riddle and find the serial killer. Yet the numbers make no sense. Are they a pattern? A formula? Or do they have no meaning at all? Zoe, reeling from her own personal troubles, hasn't the luxury of time, as more bodies pile up, and as all eyes turn to her to solve an equation that, perhaps, cannot be solved. Will she catch the killer in time? An action-packed thriller with heart-pounding suspense, FACE OF MURDER is book #2 in a riveting new series that will leave you turning pages late into the night. Book #3 in the series-FACE OF FEAR-is also available for pre-order.
Keywords: Krimi, detektivky